Worksout in intermediate microeconomics - Begstorm Theodore C.; Varian Hal R. (New York : W. W.Norton & Company, 1996)
This volume provides valuable assistance to those using Varian's Intermediate Microeconomics, Third Edition. The chapters here begin with introductions that review problem-solving techniques. They then proceed to offer one or two examples of already completed problems. Finally they leave you on your own with a variety of exercises that will help you master the economic analysis presented in the text.
aau 10/08/2022
Loan